PENGUATAN PEMBENTUKAN KARAKTER BERBASIS PERMAINAN BERHITUNG ORANG NGADA (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2020)
This paper offers the meaning of 'arithmatic game' in local traditions of Ngada. The theory being used is oral tradition theory and modification of diffusion theory neodifusionist who shows the encounter of the spirituality values ??of muzi sadho from local religion and the 'perfect life' spirituality of the Roman Catholic Church. The nine spirituality hierarchies are found in the meaning of ‘arithmetic game’ can influence contemporary Ngada people to strengthen the formation of his human character to fight the phenomenon of public outragein the new millennium era.
Keywords: Arithmatic game; spirituality; character